Culture and the creative economy in Emilia-Romagna, Italy (OECD Local Economic and Employment Development (LEED) Papers, 2022)
Cultural and creative sectors are a significant driver of local development through job creation and income generation, spurring innovation across the economy. Beyond their economic impacts, they also have significant social impacts, from supporting health and well-being to promoting social inclusion and local social capital. This paper offers a review of cultural and creative sectors in the Emilia-Romagna region, Italy, highlighting issues and trends in regards to employment, business, entrepreneurship and financing in cultural and creative sectors. It also reviews issues and trends relating to cultural participation and offers in-depth analysis on the role of museums in supporting local development. The paper provides analysis and recommendations to support the region in strengthening the local cultural and creative ecosystem